We are given the following functions;
![\begin{gathered} p(x)=3x-2 \\ q(x)=2x+5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kt6yjubxtzoo42s7tkbf21maveqq9njw1z.png)
We shall find the values of the following;
![p(x)-q(x)](https://img.qammunity.org/2023/formulas/mathematics/high-school/xxo0xp99vmum8i4efvfsbkohydwpc17bvp.png)
We substitute for the values of each function and we'll have;
![\begin{gathered} p(x)-q(x)=(3x-2)-(2x+5) \\ p(x)-q(x)=3x-2-2x-5_{} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/i005gyc7pkpg3deuyp6x5s0jd54mkv3dxh.png)
Take note that the negative sign in front of the parenthesis affects both values. Hence negative +5 becomes -5. We now have;
![\begin{gathered} p(x)-q(x)=3x-2-2x-5 \\ p(x)-q(x)=3x-2x-5-2 \\ p(x)-q(x)=x-7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7x5xn4xig8npamwmws9afx4dvbjlkbgj40.png)
(B):
![p(x)+q(x)](https://img.qammunity.org/2023/formulas/mathematics/college/h5cflrct82nlbpjt3ahchv5s9jhtdlku9y.png)
Just like in part (a), we shall substitute for the value of each of the functions, as follows;
![\begin{gathered} p(x)+q(x)=(3x-2)+(2x+5) \\ p(x)+q(x)=3x-2+2x+5 \\ p(x)+q(x)=3x+2x+5-2 \\ p(x)+q(x)=5x+3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/z4o9f0sxex5neq1oi1ie75j0zywealwvyl.png)
(C):
![p(x)q(x)](https://img.qammunity.org/2023/formulas/mathematics/college/u8a3qvzg5tnehdyrn7qqduud609zm065w3.png)
In this case, we calculate the product of both functions, and we start by substituting for the value of each;
![\begin{gathered} p(x)q(x)=(3x-2)(2x+5) \\ p(x)q(x)=3x\cdot2x+3x\cdot5-2\cdot(+2x)-2\cdot(+5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d3n6jnk0n21fs00dag69iansjnk4ene0p3.png)
We can now simplify the above and we'll have;
![\begin{gathered} p(x)q(x)=6x^2+15x-4x-10 \\ p(x)q(x)=6x^2+11x-10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vlwtxvak1eiv5mgyxwmymy0vx2v3q27woo.png)
ANSWER:
![\begin{gathered} (a)=x-7 \\ (b)=5x+3 \\ (c)=6x^2+11x-10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/80rui6hras435zekq2ovs8uflh6e7eniqy.png)